Real estate valuation : a subjective approach - Goddard, G. Jason (New York, NY : Routledge, 2021)
"Real Estate Valuation: A Subjective Approach highlights the subjective valuation components of residential and commercial real estate which can lead to a range of acceptable property value conclusions. It discusses the causes of housing booms and goes in depth into the heterogeneity of commercial real estate property valuation via examples from owner occupied, multi-family residential, hotel, office, retail, warehouse, condo conversion, and mortgage backed securities areas of real estate. Other topics explored include the role of machine learning and AI in real estate valuation, market participant value perceptions, and the challenge of time in the valuation process. The primary theoretical basis for the range of acceptable values and the subjectivity of property valuation focuses on the work of G.L.S. Shackle from the Austrian School of Economics"--
Keywords: Real property -- Valuation; Information technology -- Management; Artificial intelligence -- Economic aspects; BUSINESS & ECONOMICS / Finance; BUSINESS & ECONOMICS / Real Estate